Resection of an Extraovarian Noniuteinized Thecoma in a 14-Year-Old Girl - Aubert, Ophelia; Wachowiak, Robin; Roth, Christian; Höhn, Anne K.; Lacher, Martin; Mayer, Steffi (European Journal of Pediatric Surgery Reports, 2022)
Thecomas are rare benign sex cord-stromal tumors that account for less than 1% of all ovarian tumors. They usually affect postmenopausal women and become symptomatic with abnormal bleeding. In adolescents, less than 10 cases have been reported so far, mainly with symptoms of hormonal disbalance. Extraovarian thecomas represent an even rarer entity, with only two cases described so far, none of them in the pediatric population.We report the case of a 14-year-old girl who presented with sudden-onset abdominal pain, dysuria, and fever, as well as highly elevated serum inflammation parameters. Ultrasound and magnetic resonance imaging (MRI) revealed a large, inhomogeneous pelvic mass (16 cm × 9 cm × 13 cm) with indistinct margins, suggestive of an infiltrative malignant teratoma or sarcoma. Laparoscopy confirmed a large mass of unknown origin. In contrast to the infiltrative character seen on preoperative MRI, the tumor could be easily exteriorized and resected after conversion to laparotomy. Ovaries, fallopian tubes, and uterus remained unaffected. Histopathology revealed a benign nonluteinized thecoma. The postoperative course and 19-month follow-up were uneventful.
Keywords: ovarian neoplasm; extraovarian thecoma; adolescent